2014
DOI: 10.1093/infdis/jiu118
|View full text |Cite
|
Sign up to set email alerts
|

Periportal CD4+ Cell Infiltration Increases in HIV/Hepatitis C Virus-Coinfected Patients Commencing ART, Whereas CD8+ Cells Clear From the Liver

Abstract: Coinfection with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) is common in Asia, but the effects of antiretroviral therapy (ART) are unclear. Histopathological changes in the liver are described in a prospective study of HCV-seropositive HIV-infected patients at Cipto Mangunkusomo Hospital (Jakarta, Indonesia). Liver biopsy specimens were collected at baseline (n = 48) and 48 weeks (n = 34). Ishak scores showed mild but detectable inflammation and/or fibrosis. Levels of portal inflammation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Similar CD56 + lymphocyte numbers in patients with and without HCV IRD is consistent with the lack of any association between IRD and hepatic CD4 + and CD8 + cells in this cohort. 9 This study showed that CD56 + lymphocytes were rare or absent in the livers of HIV/HCV co-infected patients and their numbers did not rise during ART. NK and NKT cells can produce IFN-γ and inhibit fibrogenesis.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…Similar CD56 + lymphocyte numbers in patients with and without HCV IRD is consistent with the lack of any association between IRD and hepatic CD4 + and CD8 + cells in this cohort. 9 This study showed that CD56 + lymphocytes were rare or absent in the livers of HIV/HCV co-infected patients and their numbers did not rise during ART. NK and NKT cells can produce IFN-γ and inhibit fibrogenesis.…”
mentioning
confidence: 59%
“…7 Two reports of a prospective cohort of HIV/HCV patients treated in Jakarta, Indonesia, examined the effects ART and IRD. 8,9 Yunihastuti et al 8 showed that a plasma marker of T-cell activation (soluble CD26) rose during HCV IRD. Gani et al 9 showed that intrahepatic CD4 + cells increased while CD8 + cells diminished after ART, but these were not predictive of IRD.…”
mentioning
confidence: 99%
See 3 more Smart Citations